PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN STUDI KAUSAL PADA PERGURUAN TINGGI LA TANSA MASHIRO RANGKASBITUNG DI KABUPATEN LEBAK - Mike Mega Rahayu (Universitas La Tansa Mashiro, 2016)
The purpose of this study was to analyze the influence of organizational culture on employee performance and motivation. At La Tansa Mashiro College. simultaneously and partially significant in improving the performance of employees at La Tansa Mashiro College. Respondents in the study conducted by taking a sample of 63 people, the data collected by using a questionnaire with a list of questions, the analysis technique. The data used is multiple regression analysis using SPSS 20 for windows. While partially variables no significant effecton the performance of employees at La Tansa Mashiro College. Based on the results of multiple regression analysis proved that the influence of organizational culture, motivation, and performance of employees simultaneously and partially significant in improving the performance of employees at La Tansa Mashiro College. The implicationsof this study, is the employee's performance. Must be improved, especially in terms of : the work must comply with the standards, the ability to complete the work and attitude of cooperationof employees in completing the work. Motivation should be strengthened, especially in terms of communication and attention superiors to subordinates, superiors support to providea good example. Employees should be improved, especially in terms of: the responsibility for the work and maintain a good working atmmosphere on the job.